2017
DOI: 10.1111/jvs.12506
|View full text |Cite
|
Sign up to set email alerts
|

Community response to alkaline pollution as an adjusting re‐assembly between alternative stable states

Abstract: Aims We hypothesize that the community response to disturbances can be interpreted as a large‐scale dynamic equilibrium between multiple alternate states stemming from different species pools within a regional meta‐pool and being limited by species’ multi‐dimensional niches. We explore this hypothesis by examining the re‐assembly of an acidophilous lichen community in response to long‐term alkaline dust pollution, assuming understorey as a potential side‐factor. Location Around a cement factory in Kunda, Eston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Biomass contains a lot of water, which will form pores after drying, and will further decompose to form hierarchical pores with a highly specific surface area during carbonization, providing rich active sites and favoring mass transportation [14]. To further produce pores, KOH or NaOH as a pore-forming agent was used to corrode carbon [15,16]. In addition, biomass materials contain heteroatoms such as N, P, O and C. It is reported that heteroatom-doped carbons display similar ORR activity to Pt/C [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass contains a lot of water, which will form pores after drying, and will further decompose to form hierarchical pores with a highly specific surface area during carbonization, providing rich active sites and favoring mass transportation [14]. To further produce pores, KOH or NaOH as a pore-forming agent was used to corrode carbon [15,16]. In addition, biomass materials contain heteroatoms such as N, P, O and C. It is reported that heteroatom-doped carbons display similar ORR activity to Pt/C [17,18].…”
Section: Introductionmentioning
confidence: 99%